Pendidikan Konservasi Satwa Endemik Sulawesi bagi Siswa Sekolah Dasar di Desa Palaes, Kecamatan Likupang Barat, Kabupaten Minahasa Utara - Saroyo Sumarto; Parluhutan Siahaan; Adelfia Papu (The Studies of Social Sciences, 2022)
Â Conservation education is important for early childhood because at this stage of development, they are easy to get influenced by external factors, especially on topics that are interesting for them and are able to generate interest and attention. North Sulawesi which is part of the Walllacea Region with high biodiversity with forms of endemism, especially animals, has provided uniqueness and benefits for the area. On the other hand, the high threat to their survival has become an international concern. Therefore, it is very important to implement conservation efforts through conservation education at an early age. The purpose of this community service activity is an effort to socialize the existence, benefits, threats, and conservation that can be done from an early age. The method of implementing the activity is through workshops on examples of Sulawesi endemic animals in North Sulawesi, threats to their survival, and conservation efforts. The evaluation was carried out through a simple pretest and posttest on knowledge and attitudes towards the diversity of Sulawesi endemic animals and their conservation. The results of the evaluation showed that there was an increase in knowledge from 3.8 to 6.2 and attitudes from 5.6 to 6.4. The conclusion of the activity is an increase in knowledge and attitudes of elementary school students towards knowledge and conservation of Sulawesi's endemic animals in North Sulawesi.Keywords: Conservation education; elementary school students; Sulawesi endemic animals; Palaes Village; North MinahasaAbstrakPendidikan konservasi penting bagi usia dini karena pada tahap perkembangan tersebut, mereka mudah untuk mendapatkan pengaruh faktor luar, apalagi pada topik-topik yang bagi mereka menarik dan mampu memunculkan minat dan perhatian. Sulawesi Utara yang merupakan bagian dari Kawasan Walllacea dengan keanekaragaman hayati yang tinggi dengan bentuk-bentuk endemisme, terutama satwa telah memberikan kekhasan dan manfaat bagi kawasan. Di sisi lain, tingginya ancaman terhadap kelangsungan hidup mereka telah menjadi keprihatinan dunia internasional. Oleh karena itu upaya konservasi melalui pendidikan konservasi pada usia dini sangat penting untuk dilaksanakan. Tujuan kegiatan pengabdian kepada masyarakat ini ialah upaya untuk sosialisasi keberadaan, manfaat, ancaman, serta konservasi yang bisa dilakukan sejak usia dini. Metode pelaksanaan kegiatan ialah melalui workshop contoh-contoh satwa endemik Sulawesi di Sulawesi Utara, ancaman terhadap kelangsungan hidupnya, serta upaya konservasinya. Evaluasi dilaksanakan melalui pretes dan postes sederhana terhadap pengetahuan dan sikap terhadap keanekaragaman satwa endemik Sulawesi dan konservasinya. Hasil evaluasi menunjukkan bahwa terjadi peningkatan pengetahuan dari 3,8 menjadi 6,2 serta sikap dari 5,6 menjadi 6,4. Kesimpulan hasil kegiatan menunjukkan bahwa pengetahuan dan sikap meningkat pada siswa sekolah dasar terhadap pengetahuan dan konservasi satwa endemik Sulawesi di Sulawesi Utara.